Early trade-offs and top-level design drivers for Antarctic greenhouses and plant production facilities - Bamsey, Matthew; Zabel, Paul; Zeidler, Conrad; Vrakking, Vincent; Schubert, Daniel; Kohlberg, Eberhard; Stasiak, Michael; Graham, Thomas (2016)
The development of plant production facilities for extreme environments presents challenges not typically faced by developers of greenhouses in more traditional environments. Antarctica represents one of the most inhospitable environments on Earth and presents unique challenges to facility developers with respect to environmental regulations, logistics, waste management, and energy use. The unique challenges associated with plant production in Antarctica heavily influence the selection of subsystem components and technologies as well as the operational paradigms used to operate the facilities. This paper details a wide array of the early design choices and trade-offs that have arisen in the development of Antarctic plant production facilities. Specific requirements and several guidelines stemming from the Antarctic Treaty’s Protocol on Environment Protection and their influence on Antarctic plant production facilities are described. A review of guidelines for Antarctic greenhouses published by several national Antarctic operators is also described. The specific technology choices of several past and present Antarctic greenhouses are summarized, as are the general operational strategies, such as solid and nutrient solution waste handling. Specific lessons learned input was compiled directly from developers and operators of a number of these facilities. A discussion on the Antarctic climate, differences in Antarctic installation locations, internal versus external station plant growth facilities, preshipment testing programs, carbon dioxide enrichment and numerous other Antarctic facility design trade-offs are elaborated. It is hoped that this paper can serve as a useful checklist for future Antarctic plant production facility developers.